Challenges and interventions in water resource management for horticultural crop production in rural and tribal communities in India - Muganyizi J. Bisheko; Rejikumar G (Cogent Food & Agriculture)
This study aims to investigate the multidimensional challenges faced by farmers in Ransai village in managing water for agriculture and to identify practical interventions for sustainable agricultural water management. Employing a qualitative approach, the study used participant observations to obtain current information on farming practices and daily issues encountered by farmers, resource mapping and transect walks to understand the spatial challenges associated with water management and distribution of the village’s water sources, and focus group discussions (FGDs) to capture the collective perspectives of farmers. In addition, the Crop Water Assessment Tool (CropWat model) was utilized to determine the irrigation and crop water requirements for the main horticultural crops cultivated in the study area. The study identified various critical challenges, including water scarcity, lack of rainwater harvesting systems, outdated irrigation methods, lack of land ownership, limited agricultural extension services, land fragmentation, fragmented community efforts, limited access to credit, cultural practices and beliefs, and insufficient knowledge of water conservation practices. The intricate and intertwined nature of these challenges necessitates a multipronged approach to help farmers navigate them and achieve sustainable agricultural water management. The findings of this study provide policymakers and other relevant stakeholders with practical insights that can guide the development of targeted interventions for enhancing water management in tribal agricultural settings.